Mula pabrika hanggang Fukuoka [videorecording] - Policy, inihahandog ng Ateneo Center for Social; Carolino, Ditsi; Buxani, Sadhana; Center, Public Affairs at ng Archdiocese of Manila Labor (Quezon City The Center, 1999)
A documentary on the personal narratives of Filipino women working in a manufacturing firm in the Philippines and in Japan.
A Special mention citation in the Yamagata International documentary film festival in Japan.
This documentary was made possible with a grant from MISSIO.
VHS.
Also available in CD format.
Keywords: Carolino, Ditsi; Buxani, Sadhana; Ateneo Center for Social Policy Center; Archdiocese of Manila Labor Center; Filipino women -- Employment -- Philippines; Filipino women -- Employment -- Japan; Filipino women -- Social conditions